Les Vicissitudes de l’Entreprise et la Stabilite de l’Emploi en Droit Camerounais (African Journal of Law and Politics, 2025)
If job security remains strong, job stability continues to be a subject of concern. There is only a weak relationship between the objective indicator of job security and this is sustainability and the perception of it by people across the country. Thus, « there is a positive relationship between decent work and job security ». Job security can be generated by its stable nature, but when a recession looms or structural changes accelerate, job stability risks being jeopardized. In these situations, employees have need to rely on their social protection systems. But, it is obviously with a view to securing employment that the legislator provides conciliatory techniques between the employer and employees in order to stabilize employment. As a result, we are considering a revitalization of working conditions by modifying contractual provisions. Furthermore, even in the event of a change in the legal situation of the employer, the principle remains that of the continuation of the current contract